A novel microstructure design for high-performance structural materials with high strength and high ductility. Issue 4 (1st October 2016) - Vajpai, Sanjay Kumar; Yu, Han; Ota, Mie; Ameyama, Kei
Abstract: Creation of 'Harmonic Structure (HS)' in metals and alloys is a new material design paradigm allowing the enhancement of structural performance. In the present study, near full density compacts with HS were prepared to investigate the effect of such a bimodal microstructure on the commercially pure metals. The mechanical milling (MM) was used to obtain bimodal structure in the metal powders, i.e. ultra-fine-grained (UFG) region on their periphery, or 'Shell', and coarse-grained (CG) region in the centre or 'Core'. Subsequent consolidation of the MM powders by Spark Plasma Sintering process resulted in sintered compacts with an interconnected three-dimensional network of UFG structure along with dispersed CG areas. In other words, they demonstrated heterogeneous yet well organised and fully controllable HS. The creation of bimodal harmonic structure in pure metals exhibited considerably higher yield strength and ultimate tensile strength as compared to their homogeneous coarse-grained counterparts. Moreover, the improvement in strength was achieved without compromising the uniform deformation limit and overall ductility of the materials. Finally, numerical simulations were carried out to reveal the deformation behaviour of harmonic structured materials. The results of numerical simulations are presented and discussed.